Dysregulated myokines and signaling pathways in skeletal muscle dysfunction in a cigarette smoke–induced model of chronic obstructive pulmonary disease - Zhang, Lijiao; Li, Chunxiao; Xiong, Jing; Chang, Chun; Sun, Yongchang (Frontiers in Physiology, 2022)
Skeletal muscle dysfunction is an important extra-pulmonary comorbidity of chronic obstructive pulmonary disease (COPD). Muscle-derived cytokines (myokines) play important roles in skeletal muscle growth and function, but their contributions to skeletal muscle dysfunction in COPD have not been fully understood. In the current study, by using a well-established mouse model of COPD with skeletal muscle dysfunction, we found that the expression of Fndc5 (the precursor of irisin) and peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α) were decreased, while myostatin (Mstn), phosphorylated extracellular regulated kinase (p-Erk1/2), and p-Smad3 expressions were up-regulated in skeletal muscles from CS-exposed mice and in CSE-stimulated C2C12 myotubes. Treatment with Smad3 or Erk1/2 inhibitors partially restored expression of Fndc5 in CSE-stimulated C2C12 myotubes. Taken together, CSE exposure, by upregulation of p-Erk1/2, promoted expression of Mstn, which further inhibited Fndc5 expression by the p-Smad3/PGC-1α pathway, revealing a novel regulating mechanism of myokines in the pathogenesis of skeletal muscle comorbidities of COPD.